INTRODUCTION TO THE PROCEEDINGS VOLUME OF THE SECOND RUSSIA–CHINA INTERNATIONAL MEETING ON THE CENTRAL ASIAN OROGENIC BELT - D. P. Gladkochub; T. V. Donskaya (Геодинамика и тектонофизика, 2017)
Second Russia-China International Meeting on the Central Asian Orogenic Belt (September 6–8th, 2017, Irkutsk, Russia) with post-conference excursion (September 9–12th, 2017, Baikal area, Siberia, Russia) continues tradition of the Russian-Chinese conferences begun in 2015.